PEMBUATAN DAN PENGUJIAN KUALITAS KOMPOS DI SUBAK TIBUBIYU KECAMATAN KERAMBITAN KABUPATEN TABANAN - Narka, I.W.; `Dibia, I.N.; Kusmawati, T.; Atmaja, I.W.D. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana MengabdiDO - 10.24843/BUM.2018.v17.i01.p27, 2018)
Devotion in the form of training of composting with existing materials around the farmers using 3 starter that is EM4, MOL and Nitrobacter TJ has been done in Subak Tibubiyu, Kerambitan Tabanan. After subsequent composting is testing the quality of the three types of compost produced. The topic of composting and compost quality testing is selected based on the farmers' demand because it is pointed out by the organic fertilizer farmers that the packaging is obtained in the form of aid, the quality is not good. Is a problem also in terms of transport to the planting area? Therefore, it is necessary to make compost near the farmer's cultivation area. In improving the quality of compost has been tried to make compost with 3 types of starter and then done the quality of compost testing. Farmers welcomed this activity and were interested to find out which type of starter was best composted. After fermentation for 6 weeks the compost has matured, then the quality of the compost is tested. The results of compost testing in the laboratory show that the best compost quality is compost with EM4 starter. With the success of farmers to make their own good quality compost fertilizer, the acceleration of organic fertilizer will be done. The use of compost fertilizer can reduce the use of chemical fertilizers and maintain the sustainability of the soil.